Praktik Perhitungan Zakat Perdagangan pada UMKM: Studi Kualitatif tentang Kesadaran dan Keberlanjutan Usaha dalam Perspektif Ekonomi Syariah - Valentina Monoarfa; Afra Amatullah Bauna; Nirfa Celia Malureng; Ronal Baruadi (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Zakat is an important instrument in Islamic economics, serving as both an act of worship and a social and economic role in society. One type of zakat that must be paid is trade zakat, imposed on assets from business activities that have reached the nisab (minimum threshold) and haul (limit). MSMEs play a significant role in the regional economy and have the potential to collect trade zakat. This study aims to analyze the practice of calculating trade zakat among MSMEs in Gorontalo City and its compliance with Islamic economic principles. This study used a qualitative approach with field research methods through interviews, observation, and documentation. The results showed that most MSMEs do not yet understand the details of the nisab, haul, and how to calculate trade zakat, although some still strive to pay zakat or charity from their business profits. Therefore, increased socialization and education regarding trade zakat are needed so that MSMEs can implement it in accordance with Islamic economic principles.